Methodological Proposal in the Teaching of Physics for Developing the Mathematical Bases of 10th Grade Students in a High School of Heredia - Piedra Pereira, Evelyn (2011)
Teaching physics in Costa Rica has a number of problems which causes the students to lose interest in this science; one of them is students' poor mathematical foundations at tenth grade, as well as there is no physical reasoning and there is a lack of analysis during solving problems. Against this requirement, this research is to design a proposal to improve the teaching-learning process and to know the attitude of the students during a physics lesson, likewise, achieve a development of the mathematical foundations of students.